Intellectual capital performance of Sharia banks: Evidence from Indonesia - Yulia Tri Anggani; Ari Kuncara Widagdo (Jurnal Keuangan dan Perbankan, 2019)
Towards a sustainable Islamic banking industry must be attended by the sharia governance of capital allocation. In addition, Islamic banking requires a higher level of intellectual ability, especially intellectual capital in humans to support product innovation. The aims of this paper is to examine effect of corporate governance, family ownership structure, foreign ownership structure, and digital banking on Intellectual Capital (IC) Performance in Indonesian Islamic banks. Testing and analysis uses Least Square Panel data regression with panel data and a total of 93 observations in period 1999-2016. In this research, IC performance used Islamic Banking Value Added Intellectual Coefficient (IBVAIC). We present empirical evidence that corporate governance had significant implications for improving IC performance. In addition, digital banking negatively influences IC performance. In contrast, family ownership, foreign ownership, liquidity and age did not affect IC performance. This study to contribute literature to the IC performance in sharia banking in the form of a Sharia Business Entity.JEL Classification: G31, G32, G34DOI: https://doi.org/10.26905/jkdp.v23i4.3563